Language, Gender Bias and Identity in Arabic Language Learning - Qushayyi Akbar Editia; Zakiah Muftie Daradjah; Shofil Fikri (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
This research aims to determine the relationship between language, gender bias and identity in Arabic language learning. Language and gender cannot be separated in a context, as aspects of language, including structure, word use, and communication conventions, can play a role in forming and reproducing gender norms, including in Arabic language learning. This research method uses library research with a qualitative approach. The data that will be presented is descriptive and analytical by paying attention to the characteristics of data sourced from articles, journals, books and related discussion topics. The results of this research show that in Arabic language learning there is still an unequal gender overlap in the context of texts which are exemplified by the dominance of muzakkar rather than muannats contained in the MTs Arabic language book Class VII Print -1 of 2020. Meanwhile, language and gender must have balance and Language equality is not only a means of communication, but also a reflection of social norms and structures, especially in learning, so that there is no gender image in the learning process.